Adding Liver Stiffness Measurement to the Routine Evaluation of Hepatocellular Carcinoma Resectability Can Optimize Clinical Outcome - Cucchetti, Alessandro; Cescon, Matteo; Colecchia, Antonio; Neri, Flavia; Cappelli, Alberta; Ravaioli, Matteo; Mazzotti, Federico; Ercolani, Giorgio; Festi, Davide; Pinna, Antonio Daniele (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Purpose Liver stiffness (LS) has been shown to be of use in chronic liver disease patients but its utility in surgical judgment still needs to be proven. A decision-making approach was applied to evaluate whether LS measurement before surgery of hepatocellular carcinoma (HCC) can be useful in avoiding post-hepatectomy liver failure (PHLF).Materials and Methods Decision curve analysis (DCA) was applied to 202 HCC patients (2008 – 14) with LS measurement prior to hepatectomy to verify whether the occurrence of PHLF grades B/C should be reduced through a decision-making approach with LS. Results Within 90 days of surgery, 4 patients died (2 %) and grades B/C PHLF occurred in 29.7 % of cases. Ascites and/or pleural effusion, treatable with medical therapy, were the most frequent complications. DCA showed that using the “expected utility theory” LS measurement can reduce up to 39 % of cases of PHLF without the exclusion of any patient from surgery that duly undergoes an uncomplicated postoperative course. LS measurement does not add any information to normal clinical judgment for patients with a low (< 10 %) risk of PHLF.Conclusion LS measurement can determine a reduction of PHLF under “expected utility theory” fulfilment. However, the degree of PHLF can be minor and “risk seeking” individuals can accept such a risk on the basis of surgical benefits.
Keywords: abdomen; liver stiffness; hepatocellular carcinoma; hepatic resection; decision analysis